2016
DOI: 10.1093/mnras/stw219
|View full text |Cite
|
Sign up to set email alerts
|

Massive star mergers and the recent transient in NGC 4490: a more massive cousin of V838 Mon and V1309 Sco

Abstract: The Galactic transient V1309 Sco was the result of a merger in a low-mass star system, while V838 Mon was thought to be a similar merger event from a more massive B-type progenitor. In this paper we study a recent optical and infrared (IR) transient discovered in the nearby galaxy NGC 4490 named NGC 4490-OT2011 (NGC 4490-OT hereafter), which appeared similar to these merger events (unobscured progenitor, irregular multi-peaked light curve, increasingly red colour, similar optical spectrum, IR excess at late ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
121
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(139 citation statements)
references
References 79 publications
17
121
1
Order By: Relevance
“…An LRN, observationally, appears with persistently redder colors than a classical nova and luminosities that range from slightly fainter than classical novae to several magnitudes more luminous (e.g., Kimeswenger et al 2002;Smith et al 2016). The physical interpretation of the LRN optical/IR outburst is the merger of a close binary (Tylenda et al 2011;Ivanova et al 2013;MacLeod et al 2017).…”
Section: V1324 Sco: a Classical Novamentioning
confidence: 98%
“…An LRN, observationally, appears with persistently redder colors than a classical nova and luminosities that range from slightly fainter than classical novae to several magnitudes more luminous (e.g., Kimeswenger et al 2002;Smith et al 2016). The physical interpretation of the LRN optical/IR outburst is the merger of a close binary (Tylenda et al 2011;Ivanova et al 2013;MacLeod et al 2017).…”
Section: V1324 Sco: a Classical Novamentioning
confidence: 98%
“…However, such events may produce luminous infrared flares (Bally & Zinnecker 2005) and may be a major source of transient luminosity, kinetic energy, and momentum feedback in the self-regulation of star formation in regions forming dense star clusters and massive stars. Smith et al (2016) found a luminous visual transient, NGC4490-OT, in the galaxy NGC4490. This object is a candidate massive stellar merger event similar to but more luminous than V838 Mon.…”
Section: Explosive Outflows and Infrared-transientsmentioning
confidence: 97%
“…The equilibrium temperature radius provides an estimate of the physical size of the hot, circumstellar dust and is given by (e.g., Smith et al 2016) is assumed for the calculation. Note that if the heating of the mid-IR emitting dust is instead dominated locally by collisions with hot electrons in a post-shock environment (e.g., Dwek 1987;Dwek et al 2008), R Eq will not reflect the physical size of the system.…”
Section: Properties Of Thementioning
confidence: 99%
“…We consider the following (possibly overlapping) hypotheses for the nature of SN2010da: an SN2008S-like transient, an outburst from an LBV/sgB[e]-HMXB, a presumed stellar merger event like V1309Sco (Tylenda et al 2011),V838Mon (Bond et al 2003, Afşar & Bond 2007)or the recently identified NGC 4490-OT (Smith et al 2016), or a low-luminosity supernova explosion (e.g., electron-capture).…”
Section: On the Nature Of Sn2010damentioning
confidence: 99%
See 1 more Smart Citation